EVALUASI PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK PADA PT TDMN - TANUGRAHA, JEVON (: 2303-1719)
â€œStandar Akuntansi Keuangan untuk Entitas Tanpa Akuntabilitas Publik (SAK ETAP)â€ is determined by the Accounting Association of Indonesia (IAI) to facilitate small and medium enterprises. PT. TDMN is aâ€Usaha Micro Kecil Menengah (UMKM)â€ company which does not have any exposure to external users, so it would be simpler to use the measurement, recognition, and accounting records. Therefore, PT. TDMN chooses to use SAK ETAP in preparing and presenting financial reports. This study attempts to discuss about the implementation of SAK ETAP in the preparation of financial reports in PT. TDMN. The purpose of the financial reports is to provide the information of financial position, financial performance and cash flow of an entity that is beneficial for a large number of users in making economic decisions by someone who is not in a position to ask for special financial reports to meet specific information needs. Because of the importance of financial reports, the financial reports are prepared in a reasonable and generally acceptable accounting principles in accordance with the actual condition of the company. The study was conducted by evaluating the implementation of SAK ETAP on PT. TDMN by matching the financial reports PT. TDMN with the principles in SAK ETAP. The results of this study indicates that the working practices of financial reports in PT. TDMN are adequate because of the reports is suitable with SAK ETAP.